Comment - Adelman, M. A. (Quarterly Journal of Economics, 1951)
Journal Article Comment Get access M. A. Adelman M. A. Adelman Massachusetts Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 65, Issue 2, May 1951, Pages 280–283, https://doi.org/10.1093/qje/65.2.280 Published: 01 May 1951